HmuS from Yersinia pseudotuberculosis is a non-canonical heme-degrading enzyme to acquire iron from heme - Onzuka, Masato; Sekine, Yukari; Uchida, Takeshi; Ishimori, Koichiro; Ozaki, Shin-ichi (Biochimica et biophysica acta. General subjects, 2017)
Some Gram-negative pathogens import host heme into the cytoplasm and utilize it as an iron source for their survival. We report here that HmuS, encoded by the heme utilizing system (hmu) locus, cleaves the protoporphyrin ring to release iron from heme. A liquid chromatography/mass spectrometry analysis revealed that the degradation products of this reaction are two biliverdin isomers that result from transformation of a verdoheme intermediate. This oxidative heme degradation by HmuS required molecular oxygen and electrons supplied by either ascorbate or NADPH. Electrons could not be directly transferred from NADPH to heme; instead, ferredoxin-NADP+ reductase (FNR) functioned as a mediator. Although HmuS does not share amino acid sequence homology with heme oxygenase (HO), a well-known heme-degrading enzyme, absorption and resonance Raman spectral analyses suggest that the heme iron is coordinated with an axial histidine residue and a water molecule in both enzymes. The substitution of axial His196 or distal Arg102 with an alanine residue in HmuS almost completely eliminated heme-degradation activity, suggesting that Fe-His coordination and interaction of a distal residue with water molecules in the heme pocket are important for this activity. [Display omitted] •HmuS and canonical HOs do not share amino acid sequence homology.•Oxidative heme degradation by HmuS generates porphyrin-ring-opening products.•Both ascorbate and NADPH can serve as electron donors for heme bound in HmuS.•Electrons are not transferred directly from NADPH to heme; instead, FNR is required.•Axial histidine and distal arginine in the heme pocket of HmuS are critical for heme-degrading activity.